Single cell analysis on microfluidic devices - Chen, Yanli (Kansas State University, 2008)
A microfluidic device integrated with valves and a peristaltic pump was fabricated using multilayer soft lithography to analyze single cells. Fluid flow was generated and mammalian cells were transported through the channel manifold using the peristaltic pump. A laser beam was focused at the cross-section of the channels so fluorescence of individual labeled intact cells could be detected. Triggered by the fluorescence signals of intact cells, valves could be actuated so fluid flow was stopped and a single cell was trapped at the intersection. The cell was then rapidly lysed through the application of large electric fields and injected into a separation channel. Various conditions such as channel geometry, pumping frequency, control channel size, and pump location were optimized for cell transport. A Labview program was developed to control the actuation of the trapping valves and a control device was fabricated for operation of the peristaltic pump. Cells were labeled with a cytosolic dye, Calcein AM or Oregon Green, and cell transport and lysis were visualized using epi-fluorescent microscope. The cells were transported at rates of [simular to] 1mm/s. This rate was optimized to obtain both high throughput and single cell trapping. An electric field of 850-900 V/cm was applied so cells could be efficiently lysed and cell lysate could be electrophoretically separated. Calcein AM and Oregon Green released from single cells were separated and detected by laser-induced fluorescence. The fluorescence signals were collected by PMT and sampled with a multi-function I/O card. This analyzing method using microchip may be applied to explore other cellular contents from single cells in the future.
Keywords: Microfluidic device; single cell; cell lysis; Chemistry, Analytical (0486)